Accelerated 15 mW pulsed‐light crosslinking to treat progressive keratoconus: Two‐year clinical results. Issue 8 (August 2017) - Mazzotta, Cosimo; Baiocchi, Stefano; Bagaglia, Simone Alex; Fruschelli, Mario; Meduri, Alessandro; Rechichi, Miguel
Abstract : Purpose : To assess the clinical and microstructural results of accelerated 15 mW pulsed‐light corneal crosslinking (CXL) to treat progressive keratoconus. Setting : Siena Crosslinking Center, Siena, Italy. Design : Prospective case series. Methods : After epithelium removal (with Epi‐Clear) and 10 minutes stromal soaking with riboflavin 0.1% hydroxypropyl methylcellulose solution, all eyes had 15 mW/cm 2 pulsed‐light epithelium‐off accelerated CXL for 6 minutes of ultraviolet‐A (UVA) irradiation (1 second on/1 second off), maintaining a total UVA exposure of 12 minutes at a fluence of 5.4 J/cm 2 . The 2‐year follow‐up examination included uncorrected (UDVA) and corrected (CDVA) distance visual acuities, Scheimpflug tomography, in vivo confocal microscopy (IVCM), and spectral‐domain optical coherence tomography (SD‐OCT). Results : The study comprised 132 eyes of 96 patients (mean age 23.7 years ± 4.3 [SD]) with stage II keratoconus. The change in UDVA and CDVA was statistically significant, from 0.51 ± 0.106 logarithm of the minimum angle of resolution (logMAR) at baseline to 0.309 ± 0.074 logMAR ( P = .0001) and 0.271 ± 0.144 logMAR at baseline to 0.135 ± 0.100 logMAR ( P = .0023), respectively. Coma values measured by Scheimpflug analysis showed a statistically significant improvement beginning with the first postoperative month ( P = .0004). The IVCM scans documented basal epithelial healing occurring 72 hours after treatment associated with the presence of subepithelial nerves. The SD‐OCT scans performed in the central 6.0 mm of corneal diameter documented a demarcation line at a mean depth of 280 ± 32 μm. Conclusion : The 15 mW/cm 2 pulsed‐light epithelium‐off accelerated CXL was effective and safe, stabilizing keratoconus progression through 2 years of follow‐up.